Discovering Best Practice Establishing Evacuation Centers for Vulnerable Populations: Findings from Australia and Japan. Issue Volume 34:Issue s1(2019) (May 2019) - Kako, Mayumi; Steenkamp, Malinda; Ryan, Benjamin; Arbon, Paul; Takada, Yosuke
Abstract : Introduction: Potentially vulnerable population groups in disasters include the elderly and frail, people who are isolated, and those with chronic diseases, including mental health conditions or mobility issues. The disasters such as the Queensland flood and Great East Japan Disaster in 2011, affected regions of Australia and Japan. This study is followed by two pilot studies in both countries after the disasters. While both countries have different evacuation center procedures for evacuees, the issues regarding the role and responsibility across governments involving planning, setup, and management of evacuation centers demonstrate similarities and differences. Aim: This paper will report the preliminary findings of a pilot study undertaken with local government officials and humanitarian agencies in Australia and Japan concerning their involvement in planning for, setting up, and managing evacuation centers for vulnerable populations in recent natural disasters. The objective is to illuminate the similarities and differences that officials and agencies faced, and to highlight the resolutions and lessons learned in the preparation of evacuation centers through this event. Methods: This is the final stage of the study. After completing an analysis of both phases, a comparative framework to highlight similarities and differences was developed. Results: Each government's role in relation to the establishment of evacuation centers is legally defined in both countries. However, the degree of involvement and communication with non-governmental organizations from the planning cycle to the recovery cycle demonstrates different expectations across governments. Discussion: While the role of governments is clearly established in both countries based on the legal frameworks, the planning, set-up, and management of evacuation center differs.